Application of Wireline Formation Tester in Moderate and Low Permeability Depleted Zones - LIU Yingming; SONG Yantuo; JIANG Yinghui; JIAO Libo (Cejing jishu)
Due to the long extraction time, some fault reservoirs in the BURUN oil field have been depleted, resulting in extremely low formation pressure. In forepart of the project, second generation WFT tool is used. With nonadjustable pretest number, rate and volume, the low permeability intervals and big differential pressure caused a lot of matters for the tool, such as low success ration and supercharge. This article is based on the basic theory of the third generation formation tester, a new method of data acquisition has been developed, which successfully implemented with Halliburton RDT tools in the oil field. The operating principle and the diffusion model which are mentioned in the article provide theoretic guides for wireline industry. Provide ideas for the development and promotion of the third-generation wireline formation tester tools.